The Three Secular Plays of Sor Juana Inés de la Cruz : A Critical Study - Schmidhuber de la Mora, Guillermo (Book collections on Project MUSE., 2000)
Sor Juana Ines de la Cruz (1648-1695) wrote poetry, prose, and plays and is considered the greatest of Mexican women writers. She was an intellectual prodigy, reportedly mastering Latin in twenty lessons, and at sixteen she entered a convent so that she might continue her learning. One of the most influential early feminists in the New World, she answered a bishop's criticism in a letter that has become a classic defense of the education of women. She collected a private library of 4,000 volumes, but when she was told that her studies were delaying the progress of her spiritual education, she.